Wpływ światowego kryzysu gospodarczego na brazylijski i meksykański przemysł samochodowy - Wójtowicz, Mirosław (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
The aim of the study is to analyze the process of economic growth and changes of Brazilian and Mexican automobile industry in years 2000-2010. Special attention was paid to the situation of those industries in the years of global economic crisis and to strategies of dealing with the production and sales slump at the turn of years 2008-2009. The analysis confirmed disparities between Brazilian and Mexican automobile industries’ response to global economic crisis. The Mexican automobile sector was strongly affected by the slump in demand for new cars on the USA market whereas the Brazilian automobile sector experienced only a small production slowdown as the national demand for new cars soared.